Notes on the english present perfective, and on its cousin, the portuguese pretérito perfeito composto - Maia, Belinda Mary Harper Sousa (1994)
The author compares the way the English Present Perfective, and its cousin, the Portuguese Pretérito Perfeito Composto, behave with different types of lexical verb. This comparison, and a reflection on the semantic and pragmatic nature of these structures, leads to the proposal that the distinction between State, Habit and Event notions of time are not as clearcut as at first appear, and a case is made for re-considering certain examples of the English Present Perfective in the light of the 'iterative' tendency typical of the Portuguese Pretérito Perfeito Composto.